Life Cycle Assessment of Raw and Fe-Modified Biochars: Contributing to Circular Economy (2023)
ABSTRACT: Abstract: Biochar is a carbonaceous material, which can be decorated with metals, that has been garnering attention to be used in the treatment of water due to its contribution to waste management and circular economy. This study presents the life cycle assessment (LCA) regarding the generation of Pinus patula raw biochar and its modification with iron (Fe-modified biochar). SimaPro 9.3.0.3 software was used to simulate the environmental impacts of both carbonaceous materials. The potential environmental effects obtained from the production of Pinus patula raw biochar were mainly ascribed to the source of energy utilized during this process. The potential impacts demonstrated that the generation of gasses and polycyclic aromatic hydrocarbons are the main concern. In the case of Fe-modified biochar, the potential environmental effects differed only in the stage of the biomass modification with the metal. These effects are associated with the extraction of Fe and the generation of wastewater. These findings provide an insight into the environmental effects linked to the production of raw and Fe-modified biochar. However, further LCA research should be performed concerning other materials and compounds than can be generated during the biomass thermochemical conversion.